Statistical profile of Holy Quran and symmetry of Makki and Madni Surras - Muhammad Khyzer Bin Dost; Munir Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
In this paper, probabilistic approach has been made in the study of Makki, Madani and Mixed Suras of the Holy Quran. Using the word-size and word-length of Ayats, these Suras are categorized by word-length and a frequency distribution is obtained. The paper highlights the constructional characteristics of the two types of Suras in the Holy Quran. We have also discussed the dispersion and shapes of word-size and word-length of Makki and Madni Surras at other compositions of Surras as introduced by Quran Mufassirs and scientists.
Keywords: 330; Quran; Statistical profile; Frequency distribution of Ayats